Awareness and Effectiveness on Drug Advocacy Program of the Department of Health Treatment And Rehabilitation Center (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
IntroductionDrug advocacy programs are vital strategies designed to combat drug abuse by providing credible information about drugs, their effects, and potential consequences. These initiatives target vulnerable individuals to foster social inclusion and heightened awareness. Despite continuous efforts to address drug-related issues, global statistics and surveys indicate a concerning increase in drug abuse cases, particularly among the youth. This study aims to evaluate the awareness and effectiveness of the Department of Health's Drug Advocacy Program, focusing on the clinical staff of San Fernando La Union Treatment and Rehabilitation Center (SFLU TRC), the Sangguniang Kabataan/local youth, and Anti-Drug Abuse Council officers of San Fernando City and San Juan, La Union. MethodologyA descriptive developmental research method was adopted for this study. Data collection utilized a modified questionnaire that underwent expert validation and reliability testing. Administered to 86 respondents, including Anti-Drug Abuse Council officers, clinical staff of SFLU TRC, and Sangguniang Kabataan/local youth, the questionnaire's ethical compliance was ensured through review by the Ethics Review Board. Statistical analysis involved weighted mean calculations for awareness and effectiveness assessment and Analysis of Variance (ANOVA) to determine significant differences between the three respondent groups. Results and DiscussionResults showed a high level of awareness among the respondents about various aspects of drug abuse. Topics such as Prevention and Management of Drug Abuse, Risks and Dangers of Drug Abuse, Drug Use, and factors contributing to drug use received high weighted mean scores, collectively indicating an extreme level of awareness across the groups. This suggests that the drug advocacy program effectively conveyed essential knowledge regarding drug abuse, its risks, and preventive measures. Moreover, the findings highlighted the substantial effectiveness of the drug advocacy program. Elements such as Advocacy Content and Structure, Advocacy Program Tools, and Resource Persons received high weighted mean scores, indicating that the program significantly increased participants' knowledge and awareness of drug abuse. Furthermore, participants demonstrated active engagement during discussions, retaining and applying knowledge in various contexts, including sports events and youth-focused activities. Meanwhile, youth leaders recognized the influence of social factors on drug abuse, while resource speakers were found to be particularly effective in engaging Anti-Drug Abuse Council officers. The role of credible resource persons, especially those with relevant experiences, emerged as a vital component in fostering effective advocacy. Conclusion and RecommendationsIn summary, the study concludes that the drug advocacy program effectively increased awareness about the dangers of drug abuse among clinical staff, youth leaders, and Anti-Drug Abuse Council officers. Furthermore, the program's structure, content, and resource persons contributed to the highly effective dissemination of knowledge. Nevertheless, variations in responses point to areas requiring further attention. To sustain and enhance awareness, it is recommended to design a drug advocacy sustainability program that accommodates the unique needs of different groups, including youth, anti-drug abuse councils, and clinical staff in rehabilitation settings. Such an approach can ensure the longevity and efficacy of anti-drug abuse initiatives, contributing to a healthier and drug-free society.
Keywords: drug advocacy program; sustainability program; drug abuse